2019
DOI: 10.1007/s10815-019-01405-0
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced X;9 translocation in an infertile male with de novo duplication Xp22.31p22.33

Abstract: Purpose Male carriers of an X-autosome translocation are generally infertile, regardless of the position of the breakpoint on the X chromosome while the pathogenicity of Xp22.3 subtelomeric duplications is under debate. To shed light into this controversy, we present a rare case, of an azoospermic male with no other significant clinical findings, in whom classical cytogenetics revealed additional unbalanced chromosomal material, at the telomere of the long arm of one homolog of chromosome 9. Methods In periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The relationship between structural chromosomal aberrations and semen is significant in different individuals. Male carriers of a balanced X‐autosome or Y‐autosome translocations are almost invariably infertile due to severe defects in spermatogenesis that result in severe oligoasthenospermia or azoospermia (Kim et al., 2012; Roumelioti et al., 2019). Previous studies have reported conflicting results regarding the relationships between reciprocal translocation, Robertsonian translocation and semen parameters for autosomal translocations (Mayeur et al., 2019; Pastuszek et al., 2015; Vozdova et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between structural chromosomal aberrations and semen is significant in different individuals. Male carriers of a balanced X‐autosome or Y‐autosome translocations are almost invariably infertile due to severe defects in spermatogenesis that result in severe oligoasthenospermia or azoospermia (Kim et al., 2012; Roumelioti et al., 2019). Previous studies have reported conflicting results regarding the relationships between reciprocal translocation, Robertsonian translocation and semen parameters for autosomal translocations (Mayeur et al., 2019; Pastuszek et al., 2015; Vozdova et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The mosaic karyotype 45,X/46,X,i(Y) (q10)/46,XX/47,XX,i(Y)(q10) reportedly contributed to azoospermia in a 38-year-old infertile man (Barnabas et al, 2018). A de novo 8.796 Mb duplication of Xp22.31-p22.33 was detected in an infertile man harbouring an X; 9 translocation (Roumelioti et al, 2019).…”
mentioning
confidence: 96%